TRADISI PANTAUAN BUNTING DALAM PERKAWINAN MASYARAKAT DESA SUKARAMI PAGARALAM - Putri Indah Sari; Mohammad Syawaludin; Sholeh Khudin (Tanjak: Sejarah dan Peradaban Islam, 2021)
This research is entitled The Tradition of Monitoring Bunting in the Sukarami Village Community of Pagaralam, from the main point of this research: 1.How is the procession of the implementation of the Pantauan Bunting tradition in the marriage of the Sukarami village community. The purpose of this study was to find out the procession of the implementation of the pregnant monitoring tradition in marriage in the Sukarami village community. To find out the changes and developments in the marriage monitoring tradition of the Sukarami village community. From the results of the research carried out, the researchers found several new things that the Bunting Monitoring Tradition is a tradition that is still carried out by the Pasemah community, especially the Sukarami village community in a series of wedding ceremony activities in the form of invitations or invitations to eat from the local community for newly married couples. . This Bunting Monitoring tradition is carried out with the aim of profiting Muji Jurai or respecting descendants, as gratitude and respect for their descendants because someone is already married, or it can also be said as a gift from the community to the bride.